Mathematics Teachers Preparation: Relevant Aspects - Fonseca Castro, Jennifer; Castillo Sánchez, Mario (Uniciencia, 2013)
The type of knowledge and experiences that mathematics teachers need to develop as part of their initial training, has been a subject of controversy and discussion. This article aims to make a literature review of the most significant theoretical issues that have been made in this area, as well as the national trends, according to some authors. Inputs presented here, summarizes important findings that has contributed during the past four decades. It is expected   that the results generate reflections among the educational community at Costa Rica on the topic and help in guiding the curriculum of mathematics teacher training of the country.